The mystery of economy: Exploring the threshold between theology and economics - Di Somma, Emilio (Review and expositor, 2019)
This article addresses the permanence of a "theological device" within the structures of economic thought. Using the work of Giorgio Agamben, this article describes how divine providence relates to the natural world; this analysis will in turn provide the basis for a reading of contemporary economics. Oikonomia, in early Christian use, becomes not only a metaphor for the divine household and God's own life, but also begins to designate God's influence both on the divine and the material spheres. Agamben interprets contemporary economics as the theoretical movement that pushes away the "transcendent" principle from the "immanent" principle, leaving the world devoid of any relation to God. This article engages Agamben's insights in a discussion about the structures of such "providential order" inherent to economic thought, and the ways it can be described as a form of "theology," alternative to the Christian worldview.